Alterations of the gut microbiota and metabolites by ShenZhu TiaoPi granule alleviates hyperglycemia in GK rats - Zhao, Jindong; Fang, Zhaohui (Frontiers in Microbiology, 2024)
ShenZhu TiaoPi granule (STG) is a compound prescription that is used in Chinese medicine for the treatment of type 2 diabetes mellitus (T2DM). Previous studies have indicated a hypoglycaemic effect, but the underlying mechanism remains unclear. Goto-Kakizaki (GK) rats were used to establish an in vivo T2DM model (Mod). The metformin (Met) and STG treatment time was 12 weeks. Fasting blood glucose (FBG) and insulin levels and the area under the glucose curve (GAUC) were measured. Intestinal pathology and permeability were observed. Microbial diversity analysis and metabolomics were used to investigate the underlying mechanisms. Compared with the Con group, the T2DM Mod group presented significant differences in weight, FBG, GAUC, and homeostasis model assessment–insulin resistance (HOMA-IR) indices (p < 0.01). Met and STG improved these indicators (p < 0.01). The pathological morphology and zonula occludens 1 protein levels in the intestines of the Mod group of rats were altered, leading to increases in the lipopolysaccharide (LPS) and interleukin-1β (IL-1β) levels. In the Met and STG groups, the intestinal conditions improved, and the LPS and IL-1β levels significantly decreased (p < 0.01). Changes in the gut microbiota and metabolites occurred in the Mod group. In the STG group, the abundance of Intestinimonas increased, and the abundance of Eubacterium coprostanoligenes decreased significantly (p < 0.05). Moreover, STG also altered 2-deoxyglucose, beta-muricholic acid and dioxolithocholic acid production. In addition, the main metabolic pathways affected by STG were bile acid biosynthesis and cholesterol metabolism. Intestinimonas, D-maltose_and_alpha-lactose may be potential biomarkers for the effects of STG. STG alleviates hyperglycaemia via the gut microbiota and metabolites in GK rats.